Super-response to cardiac resynchronization therapy reduces appropriate implantable cardioverter defibrillator therapy. Issue 8 (4th August 2017) - Killu, Ammar M; Mazo, Anna; Grupper, Avishay; Madhavan, Malini; Webster, Tracy; Brooke, Kelly L; Hodge, David O; Asirvatham, Samuel J; Friedman, Paul A; Glikson, Michael; Cha, Yong-Mei
Abstract: Aims: To determine the frequency of implantable cardioverter defibrillator (ICD) therapy following cardiac resynchronization therapy (CRT-D) implantation in super and non-super responders and whether greater improvement in left ventricular (LV) function after CRT is associated with a reduced burden in ICD therapy. Methods and results: This is a two-centre, retrospective study between January 2002 and September 2011. Patients were classified as non-super responders and super-responders based on the post-CRT ejection fraction (EF) of < 50% and ≥50%, respectively. Of 629 recipients of CRT-D, 37 (5.9%) were super-responders. Implantable cardioverter defibrillator follow-up was available for a mean duration of 6.2 ± 2.7 years. The 5-year rate of antitachycardia pacing (ATP) in super-responders was significantly lower than in non-super responders (2.7% vs. 22.1%, P  = 0.004). Super-responders also had a lower 5-year rate of appropriate ICD shock compared with non-super responders (2.7% vs. 14.3%, P  = 0.03). On multivariable analysis, factors associated with appropriate ICD therapy (ICD shock/ATP) include male gender (hazard ratio, HR 1.97, 95% confidence interval, 95% CI 1.15–3.35), secondary prevention indication (HR 2.09, 95% CI 1.13–3.85), increased baseline LV end-systolic diameter (HR 1.03 per mm, 95% CI 1.01–1.06) and higher baseline EF (HR 1.03 per %, 95% CI 1.00–1.06) while super-responder status was highly protective (HR 0.13, 95% CI 0.02–0.91). Conclusion: Recipients of CRT-D that normalize their EF have very low rates of ventricular arrhythmias requiring appropriate ICD therapy compared with those that do not.